Kampanye Gizi Berbasis Musik dalam Program Makan Bergizi Gratis - Ian Septian Raharjo (PERPROMI, 2026)
This study aims to examine the implementation and impact of a music-based nutrition campaign within the Free Nutritious Meal Program (MBG). As a national initiative designed to improve children’s nutritional status, MBG requires effective communication strategies to encourage positive eating behavior and program acceptance. This research employed a quasi-experimental design involving elementary school students participating in the program. A music-based campaign was developed in the form of educational songs promoting balanced nutrition, healthy eating habits, and awareness of the MBG objectives. Data were collected through pre-test and post-test questionnaires measuring students’ knowledge, attitudes, and behavioral intentions related to nutrition, as well as observation during program implementation. The findings indicate that the integration of music into nutrition campaigns significantly increased students’ understanding of balanced dietary concepts and strengthened positive attitudes toward consuming the provided meals. Students exposed to the music-based intervention demonstrated higher engagement and recall of nutritional messages compared to conventional verbal explanations. The participatory and repetitive nature of music facilitated message retention and emotional connection to the campaign content. The study concludes that music-based communication serves as an effective and engaging strategy for supporting behavioral change within the Free Nutritious Meal Program. The findings suggest that integrating creative musical approaches into public health campaigns can enhance program effectiveness and sustainability, particularly in school-based contexts.